Playing by ear and the tip of the tongue : precategorial information in poetry - Tsur, Reuven (Linguistic approaches to literature ;, 2012)
In our everyday life we are flooded by a pandemonium of information which consciousness organizes into more easily manageable phonetic and semantic categories. In poetry reading, however, the total effect of a poem is not only obtained by some of these categories but also by precategorial information, for which there is a growing body of empirical evidence of its psychological reality. In the Tip of the Tongue phenomenon, a great amount of diffuse precategorial information is present but fails to "grow together" into a compact word, generating a feeling of some dense, undifferentiated mass. Po.